From the board to the touch screen: the challenges of teaching History with digital artifacts (Research, Society and Development, 2020)
Digital technologies offer countless benefits to both society and school, especially cyberspace and its tools. Interaction, communication, ubiquity, information, dispersion and connectivity are just a few of them. The history teacher can no longer exclude technological artifacts from the classroom, nor ignore that his students live in an age marked by digital media, virtuality, immediacy, provisionality and inconstancy. This work consists of a bibliographical investigation whose objective is to discuss the insertion of digital technologies in the History teaching, analyzing its benefits and challenges, as well as the necessity of a methodological change for its incorporation. Through questions and reflections, and supported by authors such as Azevedo and Stamatto (2010); Fialho, Machado and Sales (2016); Arruda (2013, 2014); Bittencourt (2011) and Lévy (1996, 1999), the study develops a theoretical discussion about the theme. The study showed the need for the insertion of technologies in the History classroom, but a thoughtful insertion which considers the possibilities and challenges involved in the use of these artifacts, as well as the theoretical and methodological changes required for their use to be focused on the criticality and construction of citizenship, aiming at preparing the student to act as subject of his history.